2023
DOI: 10.1039/d3ob00161j
|View full text |Cite
|
Sign up to set email alerts
|

Two-step conversion of uridine and cytidine to variously C5-C functionalized analogs

Abstract: C5-substituted pyrimidine nucleosides are an important class of molecules that have practical use as biological probes and pharmaceuticals. Herein we report an operationally simple protocol for C5-functionalization of uridine and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Most of these methods require additional ribose protection and a final step of deprotection, which makes them costly and time‐consuming. Recently, our group reported a straightforward and effective method for the direct trifluoromethylation of uridine and cytidine (Podskoczyj et al., 2023), utilizing a radical approach documented in the literature for the synthesis of CF 3 ‐containing deoxynucleosides (Ito et al., 2017; Ji et al., 2011; Musumeci et al., 2013). Subsequently, 5‐trifluoromethylated uridine (5‐CF 3 U) and cytidine (5‐CF 3 C) were converted to the C5‐carboxyl, ester, cyano, amide, or amidine functionalized derivatives (Podskoczyj et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these methods require additional ribose protection and a final step of deprotection, which makes them costly and time‐consuming. Recently, our group reported a straightforward and effective method for the direct trifluoromethylation of uridine and cytidine (Podskoczyj et al., 2023), utilizing a radical approach documented in the literature for the synthesis of CF 3 ‐containing deoxynucleosides (Ito et al., 2017; Ji et al., 2011; Musumeci et al., 2013). Subsequently, 5‐trifluoromethylated uridine (5‐CF 3 U) and cytidine (5‐CF 3 C) were converted to the C5‐carboxyl, ester, cyano, amide, or amidine functionalized derivatives (Podskoczyj et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This article describes the two‐step approach to introduce several chemically diverse substituents at the C5 position of uridine and cytidine via CF 3 ‐functionalized derivatives (Podskoczyj et al., 2023). Basic Protocol 1 describes the synthesis and purification of 5‐CF 3 U and 5‐CF 3 C. Basic Protocol 2 outlines the conversions of trifluoromethylated uridine and cytidine ( 2a and 2b ) using oxygen and nitrogen nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Leszczynska et al also applied this 5-CF 3 conversion for the synthesis of C5-modified pyrimidine ribonucleosides. 36,37 Concerning the CF 3 group conversion, it has been reported that the CF 3 group on the aromatic ring can be converted into nitrogen-containing heterocycles. 38 Inspired by this report and our research interest in expanding the usefulness of 5-CF 3 -pyrimidine bases as a post-synthetic precursor, in this study, we report the preparation of DNA ONs containing 5-(benzimida-zol-2-yl)-and 5-(benzothiazol-2-yl)-pyrimidine bases by postsynthetic method (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%